1996
DOI: 10.1111/j.1365-2672.1996.tb03269.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of a new campylobacter selective medium (CAT) with membrane filtration for the isolation of thermophilic campylobacters including Campylobacter upsaliensis

Abstract: The newly developed CAT campylobacter selective medium employing the blood-free charcoal-based agar containing cefoperazone (8 mg l-1), amphotericin (10 mg l-1) and teicoplanin (4 mg l-1) was compared with the membrane filtration culture technique for isolation of Campylobacter spp. including Camp. upsaliensis. Nine hundred and fifty human, 275 dog and 65 cat faeces (in which modified CCDA medium was also compared) were tested. In addition, the recovery of Camp. upsaliensis from pure cultures and from spiked h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
22
2
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 22 publications
4
22
2
1
Order By: Relevance
“…Whether all C. upsaliensis isolates demonstrate this level of cefoperazone resistance is unknown. However, data from this and other studies (2,3) suggest that the sensitivity of the type strain to cefoperazone is the exception rather than the rule. Therefore, it would appear that factors other than, or in addition to, cefoperazone concentration underlie the superiority of CAT medium over mCCDA for isolating C. upsaliensis.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Whether all C. upsaliensis isolates demonstrate this level of cefoperazone resistance is unknown. However, data from this and other studies (2,3) suggest that the sensitivity of the type strain to cefoperazone is the exception rather than the rule. Therefore, it would appear that factors other than, or in addition to, cefoperazone concentration underlie the superiority of CAT medium over mCCDA for isolating C. upsaliensis.…”
mentioning
confidence: 62%
“…Using a modification of blood-free selective media containing reduced levels of cefoperazone, Aspinall et al (2,3) demonstrated recovery of C. upsaliensis on cefoperazone amphotericin teicoplanin selective medium (CAT) that was equivalent to recovery using membrane filtration and considerably superior to recovery on mCCDA. Subsequently, CAT was shown to be superior to mCCDA for the isolation of C. upsaliensis using a semiquantitative plating method (6).…”
mentioning
confidence: 99%
“…Modified selective medium containing cefoperazone at lower concentrations may better support the growth of non-C jejuni/ C coli campylobacter. 7 A cost effective alternative to PCR might be a combination of two media, as is currently used for the detection of salmonellae. For epidemiological purposes, all culture positive samples could then be tested by PCR to identify the isolates to the species level.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane filtration method has been extensively used for the isolation of Campylobacter spp. (non selective agar base e.g., blood agar base, Mueller Hinton agar, Brucella agar supplemented with 5-7% defibrinated sheep blood) [26][27][28] . Although faecal-based methods are still the most widely used and considered to be reliable detection methods for Campylobacter in animals, their detection ranges are variable with each procedure [9,[26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…(non selective agar base e.g., blood agar base, Mueller Hinton agar, Brucella agar supplemented with 5-7% defibrinated sheep blood) [26][27][28] . Although faecal-based methods are still the most widely used and considered to be reliable detection methods for Campylobacter in animals, their detection ranges are variable with each procedure [9,[26][27][28][29] . Thermophilic Campylobacter spp., C. jejuni, C. coli, C. lari and C. upsaliensis are commensally present in the intestinal flora of dogs and cats [30,31] .…”
Section: Discussionmentioning
confidence: 99%